2020
DOI: 10.1111/jssr.12690
|View full text |Cite
|
Sign up to set email alerts
|

How Do Religion and Sexual Orientation Affect Support for U.S. Presidential Candidates? Evidence from a Survey Experiment

Abstract: A growing body of research has examined how candidates’ religion or sexual orientation affect voting likelihood among the U.S. public. No systematic study, however, has focused on the combined effect of these traits. We draw on the intersectionality literature to develop and test hypotheses for this neglected, but important, combination. Results from an original survey experiment conducted in late June 2019 demonstrate that all respondents, as well as the Republican subgroup, tend to disapprove of a gay, relig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 93 publications
(104 reference statements)
1
2
0
Order By: Relevance
“…The finding is especially surprising if one considers that conservative and religious voters have traditionally been more supportive of religious candidates (Albertson 2015; Castle et al 2017; McLaughlin and Wise 2014). Our result also confounds the Buttigieg campaign’s decision to amplify the candidate’s faith, but aligns with results from Beyerlein and Klocek (2020) by showing how voters penalize a gay religious candidate.…”
Section: Subgroup Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The finding is especially surprising if one considers that conservative and religious voters have traditionally been more supportive of religious candidates (Albertson 2015; Castle et al 2017; McLaughlin and Wise 2014). Our result also confounds the Buttigieg campaign’s decision to amplify the candidate’s faith, but aligns with results from Beyerlein and Klocek (2020) by showing how voters penalize a gay religious candidate.…”
Section: Subgroup Resultssupporting
confidence: 82%
“…Mixed results emerge with regard to sexual orientation. Studies on gay and lesbian politicians running for office have considered both hypothetical candidates (Herrick and Thomas 2002; Golebiowska 2003; Beyerlein and Klocek 2020) and real candidates (Golebiowska 2002; Haider-Markel 2010; Haider-Markel et al 2020). In the case of hypothetical candidates in experiments or non-descriptive survey questions, studies have generally found a negative impact of sexual orientation on electoral chances.…”
Section: Lgbtq Candidates and Electionsmentioning
confidence: 99%
See 1 more Smart Citation